Altered expression of nuclear factor of activated T cells, forkhead box P3, and immune‐suppressive genes in regulatory T cells of generalized vitiligo patients. (23rd January 2020) - Giri, Prashant S.; Dwivedi, Mitesh; Laddha, Naresh C.; Begum, Rasheedunnisa; Bharti, Ankit H.
Abstract: The study was aimed to analyze expression of nuclear factor of activated T cells ( NFATs ), forkhead box P3 ( FOXP3), and their associated genes (s CTLA4, flCTLA4, IL10, TGFB, IL2, IL4, CD25) in regulatory T cells (Tregs) of 48 generalized vitiligo (GV) patients and 45 unaffected controls. The transcripts of NFATC1 to NFATC4, FOXP3, IL10, flCTLA4 ( p  < .0001), NFAT5 ( p  = .0003), sCTLA4 ( p  = .001), and FOXP3 protein in Tregs and plasma IL‐10 levels were reduced significantly ( p  < .0001) in GV Tregs compared to controls. The FOXP3 promoter polymorphisms [rs3761548(C > A), rs3761547(A > G), and rs2232365(A > G)] revealed significantly decreased FOXP3 protein levels in patients' Tregs with susceptible AA, GG, and GG genotypes ( p  < .0001, p  = .028, p  = .022, respectively). The active vitiligo Tregs showed reduced levels of NFATC3, NFATC4, NFAT5, FOXP3, TGFB, and flCTLA4 transcripts ( p  = .0005, p  = .0003, p  = .0002, p  = .020, p  < .0001, p  = .006, respectively) and FOXP3 and TGF‐β proteins ( p  = .0394 and p  = .0013) compared to stable vitiligo. Early‐onset patients (1–20 years) demonstrated decreased IL‐10, sCTLA‐4, flCTLA‐4, TGFB, and FOXP3 transcripts and FOXP3 protein as compared to late‐onset patients (41–60 years) ( p  = .001, p  = .003, p  = .009, p  = .005, p  = .038, p  = .0226, respectively). Overall, our results for the first time suggest a likely role of NFATs and FOXP3 together with Treg immune‐suppressive genes in GV pathogenesis and disease progression, warranting additional investigations.